Pengaruh Customer Relationship Management Terhadap Loyalitas Pelanggan Chocoffekir di Karawang - Arif Apriyanto; Syifa Pramudita Faddila (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the effect of customer relationship management on customer loyalty at Chocoffekir in Karawang City. The variables examined in this research are financial benefits, social benefits and structural ties. The analysis technique used is multiple linear regression. This study involved 150 respondents and the method used was purposive sampling. The results show that structural ties and financial benefits have a positive effect on customer loyalty. Social benefits have a positive effect on customer loyalty but not significant. Variable. Financial benefit is the variable that has the most dominant influence.